Development a Prototype Environmental Education Teacher through PAIC Process - Ruboon, On-anong; Thiengkamol, Nongnapas; Thiengkamol, Tanarat; Kurukodt, Jurairat (Richtmann Publishing, 2012)
The objective of this study was to develop a prototype of environmental education teacher through PAIC process.Sample group was selected by purposive sampling technique based on the defined criteria. The methodology was implementedwith Participatory-Appreciation-Influence-Control (PAIC) integrated with brain-storming and focus group discussion fordeveloping trainer (TOT) to be a prototype. The research results illustrated that after PAIC process implemented, the meanscores of posttest of knowledge of Environmental Education (EE), knowledge of global warming, characteristics ofEnvironmental Education Teacher (EET), inspiration of environmental conservation, environmental behavior, and trainingachievement were higher than pretest with statistical significance (p< .01, p< .01, p<.01, p< .01, p< .01, and p< .01) respectively.Furthermore, FDE was used for trainer role play evaluation, it illustrated that Trainer Self-Evaluation, Audience Evaluation,Trainer Friend-Evaluation and Expert Trainer-Evaluation were no differences among four dimensional aspects of evaluation,then the 10 selected scientific teachers with top ten highest scores to be trainers. One-way ANOVA was used investigate themean scores difference of four groups. The results of One-way ANOVA showed that there were difference of mean scores onrole play as trainer in training process (p>.05). The 10 trained scientific teachers would be prototype of EET trainers and the leftparticipants would be facilitators for the second level and they acted as steering committee to organize the second level trainingwith the aid of researcher team.